Exosomes based advancements for application in medical aesthetics - Zhang, Bin; Gong, Jianmin; He, Lei; Khan, Adeel; Xiong, Tao; Shen, Han; Li, Zhiyang (Frontiers in Bioengineering and Biotechnology, 2022)
Beauty is an eternal pursuit of all people. Wound repair, anti-aging, inhibiting hyperpigmentation and hair loss are the main demands for medical aesthetics. At present, the repair and remodeling of human body shape and function in medical aesthetics are often achieved by injection of antioxidants, hyaluronic acid and botulinum toxin, stem cell therapy. However, there are some challenges, such as difficulty controlling the injection dose, abnormal local contour, increased foreign body sensation, and the risk of tumor occurrence and deformity induced by stem cell therapy. Exosomes are tiny vesicles secreted by cells, which are rich in proteins, nucleic acids and other bioactive molecules. They have the characteristics of low immunogenicity and strong tissue penetration, making them ideal for applications in medical aesthetics. However, their low yield, strong heterogeneity, and long-term preservation still hinder their application in medical aesthetics. In this review, we summarize the mechanism of action, administration methods, engineered production and preservation technologies for exosomes in medical aesthetics in recent years to further promote their research and industrialization in the field of medical aesthetics.